The effects of training on fatique and twitch potentiation in human skeletal muscle - Herzog, W.; Rassier, D. E. (European Journal of Sport Science, 2001)
Twitch postactivation potentiation (PAP) in skeletal muscle is a well recognized and accepted phenomenon. However, the mechanisms responsible for potentiation are not understood in detail, and the possible role of potentiation in normal human movement has remained unclear. It is known that potentiation is increased in fatigued compared to rested muscle. We hypothesized that if fatigue and potentiation were directly linked, a training program should increase PAP and reduce fatigue in parallel. Six subjects underwent a muscle stimulation protocol in which twitch contractions were elicited in the knee extensor muscles before and after a 10-s maximal voluntary contraction (MVC) to detect the degree of PAP. This was done before and after subjects underwent a protocol designated to induce low-frequency fatigue (knee extensions at 180 · s-1, organized in three repetitions of 60-s bouts, separated by 3 min). This whole protocol was done before and after a 4-week period of isokinetic training, consisting of two sets (5-min interval) of 10 single MVCs (10-s intervals), at 90° · s-1. In non-fatigued muscles, PAP was greater after training (51.2 ± 4.8%) than before training (44.4 ± 2.4%). In fatigued muscles, PAP was similar before and after training (59.9 ± 2.8% and 60.2 ± 2.6%, respectively). Low-frequency fatigue was observed before training, as twitch force decreased to 66.8 ± 3.1% of the pre-fatigue value. After the training period, low-frequency fatigue was attenuated, as force decreased only to 81.8 ± 2.6% of the pre-fatigue value. Therefore, it appears that training decreases low-frequency fatigue and increases PAP. Therefore, the hypothesis that potentiation is partially linked to fatigue in voluntary contracting human skeletal muscles was confirmed.